2009
DOI: 10.1002/lt.21791
|View full text |Cite
|
Sign up to set email alerts
|

The clinical relevance of the anhepatic phase during liver transplantation

Abstract: This study assesses the relation between the anhepatic phase duration and the outcome after liver transplantation. Of 645 patients who underwent transplantation between 1994 and 2006, 194 were recipients of consecutive adult primary piggyback liver transplants using heart-beating donors. The anhepatic phase was defined as the time from the physical removal of the liver from the recipient to recirculation of the graft. Other noted study variables were the cold and warm ischemia times, donor and recipient age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 19 publications
0
45
2
Order By: Relevance
“…Delva et al thought that rewarm ischemia time should not exceed 60 minutes (Delva et al, 1989). Recently, in a logistic regression analysis by Ijtsma et al, the anhepatic phase over 100 minutes [odds ratio (OR), 4.28] was an independent predictive factor for graft dysfunction (Ijtsma et al, 2009). These results suggested that extended rewarming ischemia time is an important risk factor for IPGF.…”
Section: Rewarm Ischemiamentioning
confidence: 99%
“…Delva et al thought that rewarm ischemia time should not exceed 60 minutes (Delva et al, 1989). Recently, in a logistic regression analysis by Ijtsma et al, the anhepatic phase over 100 minutes [odds ratio (OR), 4.28] was an independent predictive factor for graft dysfunction (Ijtsma et al, 2009). These results suggested that extended rewarming ischemia time is an important risk factor for IPGF.…”
Section: Rewarm Ischemiamentioning
confidence: 99%
“…Many variables, such as massive blood loss and secondary hypotension, a prolonged anhepatic phase, and intraoperative electrolyte and acid-base disorders, may cause acute kidney injury or further impairment of the renal function. [16][17][18] Several investigations have reported that massive intraoperative allogeneic red blood cell transfusions have a negative effect on liver transplant recipient outcomes. [19][20][21] Ramos and associates 22 confirmed that massive red blood cell transfusions are associated with longer hospital stays, and decreased postoperative survival for liver transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…An anhepatic phase time of not more than 26 min has been considered to be safe for liver transplantation (Kamada and Calne, 1979), whereas a longer anhepatic phase time has been proven to be negatively associated with graft survival after transplantation (Ijtsma et al, 2009). In our study, the connection between the SHIVC and PV was prepared during the plasty of the donor liver grafts, significantly shortening the time of the anhepatic phase, so that the anhepatic phase time of the DLTs were all within 25 min.…”
Section: Discussionmentioning
confidence: 99%